f(n)=93+4(n-1)f(n)=93+4(n−1)f, left parenthesis, n, right parenthesis, equals, 93, plus, 4, left parenthesis, n, minus, 1, right parenthesis Complete the recursive formula of f(n)f(n)f, left parenthesis, n, right parenthesis.

Respuesta :

Answer: f(n) = 4n + 97 (or 97 + 4n)

Step-by-step explanation:

Distribute 4 and (n-1)

f(n) = 93 + 4n - 4

Add 93 and 4

f(n) = 97 + 4n

ekohn

Answer:

The answer is 93 & 4

Step-by-step explanation:

I got it right on khan. Btw I don't know if someone said this already bc I am sooo tired bc it's 1 am :(

ACCESS MORE